2020
DOI: 10.1111/ajr.12633
|View full text |Cite
|
Sign up to set email alerts
|

Job satisfaction of rural medical interns: A qualitative study

Abstract: ObjectiveTo study reasons for job satisfaction and dissatisfaction among interns.DesignUsing a qualitative methodology, one‐to‐one interviews were conducted with interns.SettingThe study was based at a Victorian Rural Intern Training program.ParticipantsTwelve interns from the program were interviewed during their final rotation.Main outcome measuresReasons for job satisfaction and dissatisfaction among rural interns.ResultsReasons for job satisfaction included feeling supported in the workplace as well as get… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(16 citation statements)
references
References 20 publications
0
16
0
Order By: Relevance
“…2 Internship is therefore a crucial period of learning for medical graduates during which career decisions are often made. 3 Interns are the most junior members of the medical workforce. They spend a relatively short time with each clinical team, which makes for a unique learning experience.…”
Section: Learning In the Medical Workplacementioning
confidence: 99%
“…2 Internship is therefore a crucial period of learning for medical graduates during which career decisions are often made. 3 Interns are the most junior members of the medical workforce. They spend a relatively short time with each clinical team, which makes for a unique learning experience.…”
Section: Learning In the Medical Workplacementioning
confidence: 99%
“…The influences on physician trainee supervision, long term availability of supervisors and quality of supervision in regional, rural and remote areas have received little direct research attention. Studies have examined the needs of trainees, 6,7 but the experiences of supervisors who deliver training and the integration of trainee and supervisor experiences have rarely been explored. While we have clear information about the power of a rural background and rural training in supporting the attraction and retention of rural trainees, 8-15 the entirety of the rural training experience is more complex.…”
Section: Chapter 3 Sustainable Rural Physician Training: Leadership In a Fragile Environmentmentioning
confidence: 99%
“…(JMO 4) pg 479 (45) "They lacked resources... but they have a really good work culture which I thought was really, really amazing." [9F] pg 247 (42) For some doctors the workplace culture had a negative impact on their experience in rural areas, reports of having too much responsibility early in their career had a negative impact on con dence, stress and intention to stay in a rural area.…”
Section: Workplace Culturementioning
confidence: 99%
“…It was generally accepted that larger city hospitals were better equipped with respect to clinical infrastructure and diagnostic facilities; however, most doctors thought that the resources available at smaller hospitals were adequate to meet their training needs, and some even spoke of the bene t to their clinical reasoning of having limited access to diagnostic technology, where having to 'make do' with minimal equipment resulted in their becoming more independent thinkers. pg 5 (49) "The consultant did weekly teaching; actually twice weekly teaching; So, after work hours, he would do a non-formal tutorial with the registrar and the intern, and I thought that was good...[8F] pg248 (42) In other studies, early career doctors reported wide ranging challenges accessing training including di culties with technology and the need to travel to and from training sessions. Barriers to training included; employers not prioritising training, funding limitations, heavy workloads and inadequate cover.…”
Section: Training Opportunitiesmentioning
confidence: 99%
See 1 more Smart Citation